Inhaled budesonide for adults with mild-to-moderate asthma: a randomized placebo-controlled, double-blind clinical trial - Fernandes, Ana Luisa Godoy; Faresin, Sonia Maria; Amorim, Maria Marta; Fritscher, Carlos Cézar; Pereira, Carlos Alberto de Castro; Jardim, José Roberto (São Paulo Medical Journal, 2001)
CONTEXT: Budesonide is an inhaled corticosteroid with high topical potency and low systemic activity recommended in he treatment of chronic asthma. OBJECTIVE: This study was conducted to determine the efficacy and safety of inhaled budesonide via a breath-activated, multi-dose, dry-powder inhaler. TYPE OF STUDY: Multicenter randomized parallel-group, placebo-controlled, double-blind, clinical trial. SETTING: Multicenter study in the university units. PARTICIPANTS: Adult patients with mild-to-moderate asthma that was not controlled using bronchodilator therapy alone. PROCEDURES: Comparison of budesonide 400 µg administered twice daily via a breath-activated, multi-dose, dry-powder inhaler with placebo, in 43 adult patients (aged 15 to 78 years) with mild-to-moderateasthma(FEV171%ofpredicted normal) that was not controlled using bronchodilator therapy alone. MAIN MEASUREMENTS: Efficacy was assessed by pulmonaryfunction tests and asthma symptom control (as perceived by the patients) and the use of rescue medication. RESULTS: Budesonide 400 µg (bid) was significantly more effective than placebo in improving morningpeakexpiratoryflow(meandifference: 67.9 l/min; P < 0.005) and FEV1 (mean difference: 0.60 l; P < 0.005) over the 8-week treatment period. Onset of action, assessed by morning peak expiratory flow, occurred within the first two week sof treatment. CONCLUSIONS: Budesonide via a breath-activated, multi-dose,dry-powder in haler results in a rapid on set of asthma control, which is main tained over time and is well tolerated in adults with mild-to- moderate asthma.